Topical 5% minoxidil versus topical 0.2% glyceryl trinitrate in treatment of chronic anal fissure: A randomized clinical trial. (March 2020) - Emile, Sameh Hany; Abdel-Razik, Mohamed Anwar; Elshobaky, Ayman; Elbaz, Samy Abbas; Khafagy, Wael; Shalaby, Mostafa
Abstract: Background: Chronic anal fissure (CAF) is a common painful anal condition. Medical treatment of CAF involves the use of agents that induce chemical sphincterotomy. The present trial aimed to compare the efficacy and safety of topical minoxidil and glyceryl trinitrate (GTN) preparations in treatment of CAF. Methods: Adult patients with CAF were randomly assigned to one of two equal groups; group I received topical 5% minoxidil gel and group II received topical 0.2% GTN cream. The main outcome measures were healing of anal fissure, duration to healing, relief of symptoms, and adverse effects. Results: 62 patients (36 female and 26 male) were included to the study. Group I comprised 30 patients and group II comprised 32 patients. Healing of anal fissure was achieved in 23 (76.7%) patients in group I and 15 (46.9%) patients in group II (p = 0.03). The average duration to healing in group I was significantly shorter than group II (4.1 ± 1.9 vs 5.3 ± 2.7 weeks, p = 0.048). Adverse effects were recorded in 2 (6.6%) patients in group I and 13 (40.6%) patients in group II. The post-treatment pain score in the GTN group was significantly lower than the Minoxidil group. Conclusion: Topical 5% minoxidil gel achieved greater and quicker healing of CAF and fewer adverse effects than topical 0.2% GTN cream. Post-treatment pain scores after GTN were significantly lower than minoxidil. Trial registration number: NCT03528772 Highlights: Adult patients with chronic anal fissure were randomly assigned to one of two equal groups. Group I received topical 5% minoxidil gel and group II received topical 0.2% GTN cream. Healing of anal fissure was achieved in 76.7% of patients in group I and 46.9% of patients in group II (p = 0.03). The average duration to healing in group I was significantly shorter than group II (4.1 vs 5.3 weeks, p = 0.048). Post-treatment pain scores were significantly lower after using GTN cream than minoxidil gel.